The geomorphological record of an ice stream to ice shelf transition in Northeast Greenland - Lane, T.P.; Darvill, C.M.; Rea, B.R.; Bentley, M.J.; Smith, J.A.; Jamieson, S.S.R.; Ó Cofaigh, C.; Roberts, D.H. (Earth Surface Processes and Landforms, 2023)
Understanding ice stream dynamics over decadal to millennial timescales is crucial for improving numerical model projections of ice sheet behaviour and future ice loss. In marine-terminating settings, ice shelves play a critical role in controlling ice-stream grounding line stability and ice flux to the ocean, but few studies have investigated the terrestrial lateral geomorphological imprint of ice shelves during deglaciation. Here, we document the terrestrial deglacial landsystem of Nioghalvfjerdsfjorden Glacier (79N) in northeast Greenland, following the Last Glacial Maximum, and the margin's lateral transition to a floating ice shelf. High-elevation areas are influenced by local ice caps and display autochthonous to allochthonous blockfields that mark the interaction of local ice caps with the ice stream below. A thermal transition from cold- to warm-based ice is denoted by the emplacement of erratics onto allochthonous blockfields. Below 600 m above sea level (a.s.l.) glacially abraded bedrock surfaces and assemblages of lateral moraines, ‘hummocky’ moraine, fluted terrain, and ice-contact deltas record the former presence of warm-based ice and thinning of the grounded ice stream margin through time. In the outer fjord a range of landforms such as ice shelf moraines, dead-ice topography, and ice marginal glaciofluvial outwash was produced by an ice shelf during deglaciation. Along the mid- and inner-fjord areas this ice shelf signal is absent, suggesting ice shelf disintegration prior to grounding line retreat under tidewater conditions. However, below the marine limit, the geomorphological record along the fjord indicates the expansion of the 79N ice shelf during the Neoglacial, which culminated in the Little Ice Age. This was followed by 20th century recession, with the development of a suite of compressional ice shelf moraines, ice-marginal fluvioglacial corridors, kame terraces, dead-ice terrain, and crevasse infill ridges. These mark rapid ice shelf thinning and typify the present-day ice shelf landsystem in a warming climate.
EPrint Processing Status: Full text deposited in DRO